Sulfur dioxide derivatives produce antidepressant- and anxiolytic-like effects in mice. (1st October 2020) - Shi, Xiaorui; Gao, Yuan; Song, Li; Zhao, Penghui; Zhang, Yipu; Ding, Yuanjian; Sun, Ruoxuan; Du, Yuru; Gong, Miao; Gao, Qiang; Shi, Yun; Guo, Qingjun; et al.
Abstract: Sulfur dioxide (SO2 ) can be endogenously generated from sulfur-containing amino acids in animals and humans. Increasing evidence shows that endogenous SO2 may act as a gaseous molecule to participate in many physiological and pathological processes. However, the role of SO2 and its derivatives in the central nervous system remains poorly understood. The present study explored the protective effects of exogenous SO2 derivatives (Na2 SO3 :NaHSO3, 3:1 M/M) on cellular injury in vitro by using the cell proliferation assay (MTS), cell counting kit 8 assay (CCK-8), and cyto-flow assay in the corticosterone (CORT)-induced PC12 cell injury model. We also examined the antidepressant and anxiolytic effects of SO2 derivatives on the chronic mild stress (CMS)-induced depression mouse model by using the open field test, novelty suppressed feeding test, forced swimming test, tail suspension test, and sucrose preference test. In the MTS and CCK-8 assays, we found that preexposure of SO2 derivatives significantly blocked CORT-induced decrease of cellular survival without causing any negative effects. Results from the cyto-flow assay indicated that treatment with SO2 derivatives could reverse CORT-induced early and late apoptosis of PC12 cells. Systemic treatment with SO2 derivatives produced markedly antidepressant- and anxiolytic-like activities in mice under normal condition and rapidly reversed CMS-induced depressive- and anxiety-like behaviors. In conclusion, these findings indicate that exogenous SO2 derivatives show protective properties against the detrimental effects of stress and exert antidepressant- and anxiolytic-like actions. The present study suggests that exogenous SO2 derivatives are potential therapeutic agents for the treatment of depression, anxiety, and other stress-related diseases. Highlights: SO2 derivatives exposure exerts protective effects on CORT-induced cellular injuries. SO2 derivatives exposure attenuates CORT-induced cell apoptosis. Exogenous SO2 derivatives treatment produces antidepressant-like effects in mice. Exogenous SO2 derivatives treatment produces anxiolytic-like effects in mice.